Application of Auto-Tuner Fuzzy PID Controller on Industrial Cascade Control - Philips, Nicholas; Sahlan, Shafishuhaza; Abdul Wahab, Norhaliza (ELEKTRIKA- Journal of Electrical Engineering, 2020)
In this paper, the effectiveness of a newly proposed optimized cascade control technique, utilizing fuzzy control applied to a furnace temperature model is presented. PID controllers are widely used in the process industry due to its simplicity and robustness. To improve the control scheme, cascade control is the apparent choice due to its wide application in critical applications of the industry, such as heater temperature control, compressor capacity control, heat exchanger temperature control and fractionation columns controls. From the work done, it is observed that with changes to process transfer function, the proposed design has a better adaptation and performs better than the conventional cascade PID control. The proposed design utilizes Fuzzy Logic to continuously tune each term of the PID controller. The performance of the proposed design is evaluated with respect to the conventional cascade PID controller. To evaluate the performance of each controller, the system’s stability and performance parameters such as rise time, overshoot, undershoot and settling time were determined. The entire system design is modelled using MATLAB/ SIMULINK, with the simulation results showing that the proposed fuzzy logic cascade controller has better robustness and dynamic performance than the conventional controller.